PROFILE OF ADOLESCENT BODY IMAGE EXPRESS THROUGH A HIGH CIRCULATION NATIONAL MAGAZINE (Fiep Bulletin - online, 2011)
Adolescence is one of the most challenging periods in human development, where the maturation of the body and psychosocial changes. The media, through news and information, often without scientific evidence, may endanger the health of adolescents, as well as other population groups. This study aimed to examine the body image of teenage express through a high circulation national magazine. This study is a descriptive and exploratory, based on the vehicle media magazine, which focuses on the teenager. The sample universe was composed of 26 issues of a magazine of national circulation, considering that the magazine has a biweekly edition, for the months January-December 2008 used a questionnaire, containing variables selected for study. We carried out the nutritional diagnosis by comparative analysis between body image of adolescents of the photographs printed in the magazine and the "Scale Drawings of the Human Figure Silhouettes" proposed by Stunkard et al (1983). The data were digitized, consolidated and analyzed using the program Excel for Windows 2007. Of the 26 samples analyzed, it was found that among the professionals interviewed, 45% of published editions had a nutritionist and about 5% of doctors as a consultant in food and nutrition. We found that 30.8% of analyzed images of teenagers conveyed by the magazine show thinness and 19.2% overweight. We conclude that the nutritionist was the professional recognized to talk about food and nutrition and there is a high percentage of adolescents with thinness in editions of magazines, however, the proportion of adolescents considered the appropriate weight was higher.
Keywords: Media; Adolescents; Body Image